CHEMICAL COMPOSITION OF SEDIMENT LOAD CARRIED BY RIVERS - Savenko V.S. (My University, 2007)
According to the modern theory of lithogenesis, the mobilization of suspended and dissolved materials in drainage basins is the initial stage of the formation of sedimentary rocks. The major portion of chemical elements is transported with river suspensions, including alkaline and calc-alkaline metals, which are highly mobile in the supergene zone. Nowadays, the total discharge of solid materials from continents is known fairly accurately, which is not the case for the chemical compositions of suspended and bed loads. The geochemical knowledge of river suspensions is very different for different elements. A large body of analytical data is available for the elements involved in ecological monitoring, for instance, heavy metals.